Two-experiment examination of habitual and manipulated foot placement angles on the kinetics, kinematics, and muscle forces of the barbell back squat in male lifters - Sinclair, J.; Taylor, P. J.; Shadwell, G.; Stone, M.; Booth, N.; Jones, B.; Finlay, S.; Ali, A. M.; Butters, B.; Bentley, I.; Edmundson, C. J. (Sensors, 2022)
This two-experiment study aimed to examine the effects of different habitual foot placement angles and also the effects of manipulating the foot placement angle on the kinetics, three-dimensional kinematics and muscle forces of the squat. In experiment 1, seventy lifters completed squats at 70% of their one repetition maximum using a self-preferred placement angle. They were separated based on their habitual foot angle into three groups HIGH, MEDIUM and LOW. In experiment 2, twenty lifters performed squats using the same relative mass in four different foot placement angle conditions (0°, 21°, 42° and control). Three-dimensional kinematics were measured using an eight-camera motion analysis system, ground reaction forces (GRF) using a force platform, and muscle forces using musculoskeletal modelling techniques. In experiment 1, the impulse of the medial GRF, in the descent and ascent phases, was significantly greater in the HIGH group compared to LOW, and in experiment 2 statistically greater in the 42° compared to the 21°, 0° and control conditions. Experiment 2 showed that the control condition statistically increased quadriceps muscle forces in relation to 0°, whereas the 0° condition significantly enhanced gluteus maximus, gastrocnemius and soleus forces compared to control. In experiment 1, patellofemoral joint stress was significantly greater in the HIGH group compared to LOW, and in experiment 2, patellar and patellofemoral loading were statistically greater in the control compared to the 42°, 21°, 0° and control conditions. Owing to the greater medial GRF`s, increased foot placement angles may improve physical preparedness for sprint performance and rapid changes of direction. Reducing the foot angle may attenuate the biomechanical mechanisms linked to the aetiology of knee pathologies and to promote gluteus maximus, gastrocnemius and soleus muscular development. As such, though there does not appear to be an optimal foot placement angle, the observations from this study can be utilised by both strength and conditioning and sports therapy practitioners seeking to maximise training and rehabilitative adaptations.